Online Counseling as a Service in College: A Generation Z Perspective - Dina Hajja Ristianti (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2022)
Online counseling is a service provided to students for the academic success of students in college. This research is a type of survey research where the research object is the young generation aged 15-25 years. The number of research subjects was 561 people consisting of students and university students. The data collection technique uses questionnaires to obtain data on the needs of Generation Z for online counseling. Scores are graded in percentages and grouped by “important” categories. The results showed that Generation Z’s need for online counseling was “urgently needed”. The findings of this study show that 93.7% of Generation Z (538 respondents) want online counseling as a support system for their learning success in college as much. They are comfortable doing online counseling through WhatUp social media as many as 69.9% (401 respondents) and Video Call media as much as 18.5% (106 respondents). The problem they wanted to address when doing online counseling was the most learning problems with 33.6% (193 respondents). Generation Z feels offline counseling is more convenient 65.9% (378 respondents) compared to online counseling 34.1% (196 respondents). Thus, universities can consider the needs of Generation Z for online counseling services.